Medical and physiological characteristics of divers’ specific diseases - A. P. Kazmirchuk; Ye. V. Moiseyenko; I. S. Trinka; A. V. Shvets (Український журнал військової медицини)
Introduction. Known variants of the classification of diving diseases are fragmentarily used in the development of specialized regulatory documents for diving units in terms of regulating medical tasks during diving descents without explaining the specificity of the development of pathology, which does not fully meet the needs of medical support for diving work.